a) 5/13 + 2x=3/13 b) 20%x -0.7x=15% c) 1/4 + (2x-1)2=1/2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{5}{13}+2x=\frac{3}{13}\)
\(2x=\frac{3}{13}-\frac{5}{13}=\frac{-2}{13}\)
\(x=\frac{-2}{13}:2=\frac{-2}{13}.\frac{1}{2}=\frac{-1}{13}\)
b) 20% x - 0,7x = 15%
(20% - 0,7)x = 15%
-1/2 x = 15%
x = 15% : (-1/2)
x = -3/10
![](https://rs.olm.vn/images/avt/0.png?1311)
a,\(2\left(2x-3\right)\ge5\left(2+x\right)+13\)
\(\Leftrightarrow4x-6\ge10+5x+13\)
\(\Leftrightarrow4x-5x\ge10+13+6\)
\(\Leftrightarrow-x\ge29\)
\(\Leftrightarrow x\ge-29\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu 2:
a: \(x^{10}=1^x\)
\(\Leftrightarrow x^{10}=1\)
=>x=1 hoặc x=-1
b: \(\left(2x-15\right)^5=\left(2x-15\right)^3\)
\(\Leftrightarrow\left(2x-15\right)^3\left[\left(2x-15\right)^2-1\right]=0\)
\(\Leftrightarrow\left(2x-15\right)^3\cdot\left(2x-16\right)\left(2x-14\right)=0\)
hay \(x\in\left\{\dfrac{15}{2};8;7\right\}\)
c: \(x^{10}=x\)
\(\Leftrightarrow x\left(x^9-1\right)=0\)
=>x=0 hoặc x=1
![](https://rs.olm.vn/images/avt/0.png?1311)
c , d giải nốt:
c) 2x + 3/6 = 7x - 13/15
=> (2x + 3) . 15 = (7x - 13) x 6
=> 30x +45 = 42x - 78
=> 30x - 42x = -78 - 45
=> -12x = -123
=> x = 41/4
d) 2-x/4 = 3x - 1/ - 3
=> (2-x) . -3 = 4. (3x - 1)
=> -6 - (-3x) = 12x - 4
(-6) + 4 = 12x - - (-3x)
=> -2 = 9x
=> x = -2/9
![](https://rs.olm.vn/images/avt/0.png?1311)
Rút gọn hết ta được :
a/ 41x - 17 = -21
=> 41x = -4 => x = 4/41
b/ 34x - 17 = 0
=> 34x = 17
=> x = 17/34 = 1/2
c/ 19x + 56 = 52
=> 19x = -4
=> x = -4/19
d/ 20x2 - 16x - 34 = 10x2 + 3x - 34
=> 10x2 - 19x = 0
=> x(10x - 19) = 0
=> x = 0
hoặc 10x - 19 = 0 => 10x = 19 => x = 19/10
Vậy x = 0 ; x = 19/10
Rút gọn hết ta được :
a/ 41x - 17 = -21
=> 41x = -4 => x = 4/41
b/ 34x - 17 = 0
=> 34x = 17
=> x = 17/34 = 1/2
c/ 19x + 56 = 52
=> 19x = -4
=> x = -4/19
d/ 20x 2 - 16x - 34 = 10x 2 + 3x - 34
=> 10x 2 - 19x = 0
=> x(10x - 19) = 0
=> x = 0 hoặc 10x - 19 = 0
=> 10x = 19
=> x = 19/10
Vậy x = 0 ; x = 19/10
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(2x-1\right)+\frac{3}{15}=\frac{3}{2}\)
\(\Rightarrow2x-1=\frac{3}{2}-\frac{3}{15}=\frac{13}{10}\)
\(\Rightarrow2x=\frac{13}{10}+1=\frac{23}{10}\)
\(\Rightarrow x=\frac{23}{20}\)
b) \(x+\frac{46}{15}=1,5\)
\(\Rightarrow x+\frac{46}{15}=\frac{3}{2}\)
\(\Rightarrow x=\frac{3}{2}-\frac{46}{15}\)
\(\Rightarrow x=\frac{-47}{30}\)
c) \(\left(-2x+1\right)+\frac{3}{15}=\frac{5}{3}\)
\(\Rightarrow-2x+1=\frac{5}{3}-\frac{3}{15}=\frac{22}{15}\)
\(\Rightarrow-2x=\frac{7}{15}\Rightarrow x=\frac{-7}{30}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a; -2\(x\) - 3.(\(x-17\)) = 34 - 2.( - \(x\) + 25)
- 2\(x\) - 3\(x\) + 51 = 34 + 2\(x\) - 50
2\(x\) + 2\(x\) + 3\(x\) = - 34 + 50 + 51
7\(x\) = 67
\(x\) = 67 : 7
\(x\) = \(\dfrac{67}{7}\)
Vậy \(x\) = \(\dfrac{67}{7}\)
b; 17\(x\) + 3.(- 16\(x\) - 37) = 2\(x\) + 43 - 4\(x\)
17\(x\) - 48\(x\) - 111 = 2\(x\) - 4\(x\) + 43
- 31\(x\) - 2\(x\) + 4\(x\) = 111 + 43
- \(x\) x (31 + 2 - 4) = 154
- \(x\) x (33 - 4) = 154
- \(x\) x 29 = 154
- \(x\) = 154 : (-29)
\(x\) = - \(\dfrac{154}{29}\)
Vậy \(x=-\dfrac{154}{29}\)